Analisis Yuridis Kebijakan Moda Angkutan Umum Di Kota Bandar Lampung - Patria, Riza Yudha; Susilawati, Susilawati; Kurniadi, Heri (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Transportation plays a very important role in regions, be they rural, semi-urban or urban areas in developing countries, because it provides access for people to meet their daily needs for goods and services, as well as improving socio-economic life, access to information and markets. Community and location-specific services, as well as new opportunities, are all important needs in the development process. Transportation problems in urban areas cannot be separated from the heterogeneous character of urban communities. The problem of urban transportation, in this case traffic jams, is complex because it is not only caused by physical factors, but also influences each other (reciprocally) with socio-legal factors and/or the behaviour of city residents. Therefore, overcoming traffic jams and various other transportation problems cannot be done only by arranging or improving physical transportation alone, but must also use a socio-legal approach, which can be done by enforcing traffic laws (rules) and raising awareness. people in traffic. In essence, a humane transportation system will also have a humane influence on people's quality of life